Influência de cimentos temporários na resistência de união de um cimento resinoso sobre a dentina pré-hibridizada - Lima, Márcio Ferreira; Maciel, Carolina Menezes; Correia, Ayla Macyelle de Oliveira; Griza, Sandro; de Mendonça, Adriano Augusto Melo (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
This study assessed the bond strength of a resin cement when Immediate Sealed Dentin (ISD) was contaminated by different temporary cements applying a microshear test. Forty-eight fragments of third molar crowns were mounted in acrylic resin and worn until the dentin was exposed. The substrates were sealed with a 3-step conventional adhesive system and divided into four groups (n=12): Control (without temporary cement) and three groups that used different temporary cements - Provy, RelyX Temp NE, and Provitemp. The temporary cements were removed after 7 days of storage. Resin cement RelyX ARC was applied to the contaminated substrates. Microshear bond strength was evaluated using a universal testing machine (0.5 mm/min). Data was analyzed with ANOVA and a Dunnett post-hoc test (p<0.05). Additionally, three samples from each group were prepared for scanning electron microscope analysis. Means and standard deviations of microshear bond strength (MPa) were 17.96±1.65, 16.70±1.43, 20.43±1.30 and 33.75±4.72 for Control, Provy, RelyX Temp, and Provitemp, respectively. Statistically significant difference was observed between the Control and Provitemp samples (p=0.0002). Adhesive failures were dominant (50%), followed by cohesive failures with cement (26%), and cohesive failures with dentin (24%). Residues of Provy and Provitemp were observed on the sealed dentin. Provitemp temporary cement sealing increased the microshear bond strength of the resin cement on dentin treated with IDS.
Effect of temporary cements on the bond strength of a resin cement to a pre-hybridized dentin
Keywords: Bond strength; Dental materials; Immediate dentin sealing; Resin cements